2001
DOI: 10.1073/pnas.171060098
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of mTOR reduces neoplasia and normalizes p70/S6 kinase activity inPten+/−mice

Abstract: PTEN phosphatase acts as a tumor suppressor by negatively regulating the phosphoinositide 3-kinase (PI3K) signaling pathway. It is unclear which downstream components of this pathway are necessary for oncogenic transformation. In this report we show that transformed cells of PTEN ؉/؊ mice have elevated levels of phosphorylated Akt and activated p70͞S6 kinase associated with an increase in proliferation. Pharmacological inactivation of mTOR͞ RAFT͞FRAP reduced neoplastic proliferation, tumor size, and p70͞S6 kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
354
3
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(379 citation statements)
references
References 45 publications
16
354
3
6
Order By: Relevance
“…A potential complication in the use of rapamycin in anti-cancer therapies is that in many cases, the effect of rapamycin is cytostatic and does not kill cancer cells (Neshat et al, 2001;Podsypanina et al, 2001;Law et al, 2002). We reported previously that under conditions of serum withdrawal, rapamycin induces apoptosis in MDA-MB-231 breast cancer cells (Chen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential complication in the use of rapamycin in anti-cancer therapies is that in many cases, the effect of rapamycin is cytostatic and does not kill cancer cells (Neshat et al, 2001;Podsypanina et al, 2001;Law et al, 2002). We reported previously that under conditions of serum withdrawal, rapamycin induces apoptosis in MDA-MB-231 breast cancer cells (Chen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been some successes, clinical trials with rapamycin and rapamycin derivatives such as CCI-779 and RAD-001 have been largely disappointing (Sawyers, 2003;Guertin and Sabatini, 2005). One of the problems with the use of rapamycin as an anti-cancer drug is that in most cases, rapamycin is cytostatic rather than cytotoxic and induces G 1 cell cycle arrest, rather than apoptosis (Neshat et al, 2001;Podsypanina et al, 2001;Law et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…6,43,125 Rapamycin, an inhibitor of mTOR kinase, and its analogs CCI-779 and RAD001 have been shown to have significant in vitro and in vivo antiproliferative activity against a broad range of human cancers. [126][127][128][129] Several rapamycin analogs have already been approved for use in transplant patients as immunosuppressants. 130 RAD001 and CCI-779 are currently in phase I and II trials, respectively, as anticancer agents.…”
Section: Molecular Biomarkers Based On Akt Activitiesmentioning
confidence: 99%
“…Preclinical models have suggested enhanced antitumoural activity of mTOR inhibition in PTEN-deficient tumours (Neshat et al, 2001;Podsypanina et al, 2001) and translational studies have revealed that activation of the PI3K/AKT/mTOR pathway is associated with reduced survival of glioma patients (Chakravarti et al, 2004). Consequently, this signalling pathway has been subjected to a number of single-or multi-targeted therapies including the mTOR inhibitor rapamycin or its derivatives, the 'rapalogs' everolimus (RAD001), deforolimus (AP23573), and temsirolimus (CCI-779) (Faivre et al, 2006).…”
Section: Introductionmentioning
confidence: 99%